Handbook of plastics recycling. - La Mantia, Francesco, ....- (Shawbury : Rapra, 2002)
Over the past 20 years recycling of plastics has increased dramatically. This is important not only from the environmental point of view (less landfill space is needed) but also from the economic point of view because recycling allows energy and materials to be reused. This book discusses some of the state-of-the-art techniques of recycling post-consumer plastic materials and focuses on mechanical recycling, chemical recycling and energy recovery. This book is intended for all those who are interested in recycling of post consumer plastic waste. Although, this book discusses technical aspects of recycling, the Authors have endeavoured to make this book easily understandable to anyone interested in the subject. This book enables the reader to gain a thorough grounding in all the subjects discussed and each chapter has a bibliography to allow follow up of subjects of interest. This book provides an invaluable resource for those already working in the field or for those just starting out in recycling.
Keywords: Afvalplastic; Hergebruik